2016
DOI: 10.1021/jacs.5b11015
|View full text |Cite
|
Sign up to set email alerts
|

On an Easy Way To Prepare Metal–Nitrogen Doped Carbon with Exclusive Presence of MeN4-type Sites Active for the ORR

Abstract: Today, most metal and nitrogen doped carbon catalysts for ORR reveal a heterogeneous composition. This can be reasoned by a nonoptimized precursor composition and various steps in the preparation process to get the required active material. The significant presence of inorganic metal species interferes with the assignment of descriptors related to the ORR activity and stability. In this work we present a simple and feasible way to reduce the contribution of inorganic metal species in some cases even down to ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
345
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(372 citation statements)
references
References 52 publications
(127 reference statements)
22
345
2
3
Order By: Relevance
“…In contrast, high PRR current on FeNC‐dry‐0.5 demonstrates that FeN x C y moieties are PRR‐active. This is a first major finding of the present study, enabled by the synthesis of Fe‐N‐C catalysts free of Fe particles 10b, 15…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, high PRR current on FeNC‐dry‐0.5 demonstrates that FeN x C y moieties are PRR‐active. This is a first major finding of the present study, enabled by the synthesis of Fe‐N‐C catalysts free of Fe particles 10b, 15…”
supporting
confidence: 53%
“…We also demonstrated that FeN x C y moieties and Fe@N‐C species are moderately active toward PRR, proving their possible roles in both direct (major path) and indirect 4 e − ORR pathways. Since the synthesis of Fe‐N‐C catalysts with only FeN x C y moieties,10b, 15 only Fe@N‐C particles,10a or their combination3b,3d, 17 is now controllable, the understanding of the nature of active sites for PRR provided herein offers new insights for the rational design of advanced Fe‐N‐C catalysts with high selectivity and expectedly improved durability in polymer electrolyte fuel cells. …”
mentioning
confidence: 99%
“…A significant advantage of SACs is that the well-defined single atomic site could allow precise understanding of the catalytic reaction pathway, and rational design of targeted catalysts with tailored activity (in a manner similar to homogeneous catalyst design). However, this perceived advantage has been investigated theoretically 23,24 , but has not yet been demonstrated experimentally in M-N-Cs, largely because existing M-N-Cs were generally obtained through pyrolysis of metal-, nitrogen-and carbon-containing molecular or polymeric precursors and the as-synthesized materials Articles Nature Catalysis are typically highly heterogeneous, concurrently containing single atomic metals along with crystalline particles, and crystalline and amorphous carbon [25][26][27][28] . Such structural and compositional heterogeneity poses a key obstacle to unambiguously identifying the exact atomistic structure of the active sites and to further establishing a definitive correlation with the catalytic properties that can guide the subsequent design of future generations of SACs.…”
mentioning
confidence: 99%
“…Studies of ORR-active materials show the presence of both metallic Fe and Fe–N species16242728. ORR catalysts containing a preponderance of either type of site have been recently synthesized, with catalysts suggested to feature FeN 4 species exhibiting the highest activity to date26293031. However, the active species in the vast majority of reported NPM catalysts remains unknown due to the heterogeneity present.…”
mentioning
confidence: 99%